Phytochemical Profile and Antioxidant Activity of Bandotan (Ageratum conyzoides L.) Leaves from East Kalimantan - Hajar, Ayu Iradha Umi; Indah, Marwa; Miranda, Esti; Nuraini, Indah; Kusuma, Aldi; Erika, Farah (Hydrogen: Jurnal Kependidikan Kimia, 2025)
Ageratum conyzoides L. is a wild plant known to contain secondary metabolites with potential antioxidant activity, such as flavonoids and phenolics. However, the content and activity of active compounds in the leaves of A. conyzoides growing in the Berau region, East Kalimantan, have not been extensively studied. This study aims to evaluate the phytochemical content and antioxidant activity of ethanol extracts from A. conyzoides leaves collected from the Batu Putih area, Berau. The samples, in the form of fresh leaves, were dried and ground before being extracted using the maceration method with 96% ethanol as the solvent. The resulting extract was then subjected to phytochemical screening to identify groups of active compounds and tested for antioxidant activity using the DPPH (2,2-diphenyl-1-picrylhydrazyl) method, with absorbance measured at a wavelength of 420 nm. Phytochemical screening results indicated the presence of alkaloids, phenolics, and tannins, while flavonoids, terpenoids, and triterpenoids were not detected. The antioxidant assay showed that the extract exhibited strong activity, with an IC50 value of 61.89 ppm, although it was still higher than that of vitamin C, which had an IC50 value of 26.77 ppm. In conclusion, the ethanol extract of A. conyzoides leaves from Batu Putih has potential as a natural antioxidant source and is worthy of further development in the pharmaceutical field.